Meningkatkan Motivasi Belajar Matematika Kelas 2 SDN 10 Tualang Melalui Penerapan Metode Pembelajaran Kelompok - Sudirman; Rita Afriani; Nur Azlan (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
Mathematics is one of the important subjects in elementary school. However, many students experience difficulties and lack motivation in learning mathematics. This can be caused by various factors. such as learning methods that are less attractive, material that is difficult to understand and a learning environment that is not conducive. This research aims to increase motivation to learn mathematics 2nd grade students at SDN 10 Tualang through the application of the group learning method. The group learning method was chosen because it can create a learning atmosphere that is more active, interactive and fun for students. Apart from that, the group learning method can also help students to exchange information and ideas, and increase feelings of trust. themselves and their independence. This research used an experimental research design with a single group pre-experimental design. The instruments used to measure student learning motivation were questionnaires and observations. Data were analyzed using descriptive statistics and the t test. The results of the research showed that there was an increase in the motivation to learn mathematics for grade 2 students at SDN 10 Tualang after implementing the group learning method. This increase can be seen from the questionnaire scores and observation results. This shows that the group learning method is effective in increasing motivation to learn mathematics in grade 2 students at SDN 10 Tualang.